Role of the microbiome in the normal and aberrant glycemic response. (April 2016) - Suez, Jotham; Shapiro, Hagit; Elinav, Eran
Summary: Multiple studies in the recent years suggest that the microbiome is critically important for normal host functions, while impaired host microbiome interactions contribute to the pathogenesis of numerous common disorders. Of these, much attention is recently given to the involvement of the microbiome in the pathogenesis of impaired glucose tolerance, type II diabetes mellitus (T2DM), and other metabolic disorders comprising the 'metabolic syndrome', including obesity, non-alcoholic fatty liver disease and their complications. In addition, alterations in the microbiome have been linked to the pathogenesis of type 1 diabetes mellitus (T1DM), an autoimmune disorder affecting the glycemic response, of distinct pathogenesis than T2DM. In this chapter we will discuss the roles of the microbiome in regulating the normal and impaired glycemic response in both mice and humans, and outline examples of underlying mechanisms by which the microbiome is contributing to diabetes mellitus. We will further discuss means by which the microbiome can be manipulated to develop future therapeutic interventions for hyperglycemia and its adverse effects.